ESRA19-0651 Tailored anesthesia: jigsaw puzzle regional anesthesia for sternal reconstructive procedures. We need to block only what we need to cover. (30th August 2019) - Costa, F; Pascarella, G; Alessandro, A; Del Buono, R; Prestipino, A; Antinolfi, V; Agrò, FE
Abstract : Background and aims: After cardiac surgery, sternal dehiscence occurs in 0.5–8.4% of cases. Reconstructive techniques of the chest wall are often required. Most of these patients, beside having heart disease, are obese and diabetic; general anesthesia is the current practice, but could represent a challenge for anesthesiologists. Sternal reconstruction techniques may involve different thoracic wall structures; different regional anesthesia techniques may be suitable for an effective intraoperative management. Every single technique may be compared to a piece of a jigsaw puzzle and the appropriate combination of the right pieces allows to accomplish the desired result. We describe two cases of sternal reconstruction under regional anesthesia and mild propofol sedation. Methods: Case 1: Sternal dehiscence after recent CABG in a 56 yo obese male with diabetes, hypertension, chronic renal failure and recent acute heart failure. Surgery plan: Left pec major muscle flap reconstruction. Regional anesthesia: Bilateral parasternal block (10 ml each side); left PECS1 10 ml; left serratus plane 20 ml CASE 2: Sternal dehiscence after recent CABG in a 55 yo obese female with diabetes, hypertension. Surgical procedure: Bilateral pec major muscle flap reconstruction. Regional anesthesia: Bilateral ESP block 15 ml each side at T3 level, bilateral PECS1 10 ml each side. A mixture of 2% mepivacaine 20 ml, 0, 75% ropivacaine 20 ml, saline 10 ml was used in both cases. Results: Surgery lasted about 3 hours and was concluded successfully and uneventfully with only mild propofol sedation. Conclusions: Awake surgery of thoracic wall in high risk patients is feasible. Regional anesthesia must be patient-tailored.